Cellulose and chitin composite materials from an ionic liquid and a green co-solvent. (15th July 2018) - Duan, Yaqing; Freyburger, Auriane; Kunz, Werner; Zollfrank, Cordt
Highlights: Cellulose/chitin composites are prepared from an ionic liquid solution with a biosourced sustainable co-solvent. Chitin does not deacetylate into chitosan during the dissolution process. The degree of crystallinity and the crystallite size of the cellulose/chitin composite materials depend on the chitin concentration. The composite gel containing 80 wt% chitin shows optimum mechanical properties. Abstract: We report on a method for the preparation of cellulose/chitin composite materials from the ionic liquid 1-butyl-3-methylimidazolium acetate and γ-valerolactone as a biosourced sustainable co-solvent. Element analysis and attentuated total reflectance Fourier transform infrared spectroscopy show that the average degree of acetylation of chitin in the composite materials was around 82.5%. This indicates that chitin is not deacetylated to chitosan during the dissolution process. The X-ray diffraction results show that the degree of crystallinity of the composite materials increases from amorphous to 59% with increasing chitin concentration accompanied by a developing crystallite size up to 3 nm. Mechanical testing yielded a maximum tensile stress of 4.7 MPa, an elastic modulus of 27.4 MPa and a breaking elongation of 78.7% for the composites with 80 wt% chitin. In addition, water contact angle measurements indicated that the presence of chitin rendered the materials more hydrophobic.